The Relationship Between Physical Activity And Diet With Nutritional Status In Students At The Iik Strada Indonesia Campus In Kediri City - Ana Solikah; Nurwijayanti (Universitas STRADA Indonesia, 2023)
In Indonesia, the nutritional problem that is being faced is the problem of undernutrition but more nutritional problems are starting to emerge simultaneously (double burden). Generally, adolescent age groups need enough energy to do diverse physical activities, light physical activity such as sitting or lying down, talking, reading, playing games and watching TV is more at risk of causing heart disease and blood vessels. The purpose of this study was to determine the relationship between physical activity and diet with nutritional status in students at the IIK Strada Indonesia campus in Kediri City. The method used is a quantitative method with a cross sectional type of research. The population in this study was all 7th semester fakar faculty students majoring in public health, pharmacy and hospital administration. The sample size was 42 respondents. The results of the study found a relationship between diet and nutritional status in students at the IIK STRADA Indonesia campus in Kediri City where the results of the chi-square test analysis obtained a p-value of 0.002. There is no relationship between physical activity and nutrition ststus in students at the IIK STRADA Indonesia campus in Kediri City where the results of the chi-square test analysis obtained a p-value of 0.757. ). For respondents whose nutritional status is lacking, it is recommended to increase nutritional intake according to needs and do physical activity according to their abilities. Physical activity that is done regularly such as brisk walking or jogging can reduce fat accumulation so as to reduce a person's risk of overweight conditions. Studentswhose diet is lacking and have thin nutritional status, according to the results of the existing questionnaire that this is because respondents in a day their food intake is less because their eating habits are less varied types. In addition, students in terms of eating they are too picky so that they are not controlled what they eat.